A fuzzy ant colony optimization to solve an open shop scheduling problem with multi-skills resource constraints. Issue 3 (2015) - Ciro, Guillermo Campos; Dugardin, Frédéric; Yalaoui, Farouk; Kelly, Russell
Abstract: An open shop scheduling problem based on a mechanical workshop is described here. The main objective is to find the sequence of jobs which minimizes the total flow time. For that reason, we first formulate the problem as a mixed integer linear programming model which considers different resource constraints related to the personnel assignment. Resource skills and their availability are required to process tasks. A mathematical model is described and solved optimally. Besides that, a fuzzy ant colony optimization method is proposed due to the difficulty to fix the different parameters of an ACO and improve the quality of the solution. Finally, some computational experiments are defined using the references of the literature to get efficiency of ant colony optimisation. A first kind of tests are related to the small-sized instances allowing to evaluate the general performance of the model and the algorithm while a second one involves the large-size instances showing a further evaluation of the algorithm.